Respuesta :
Answer:
Sure, if the quadratic equation has solutions \( x = 3 \) and \( x = -4 \), then it can be factored as follows:
Step-by-step explanation:
\[
(x - 3)(x + 4) = 0
\]
Expanding this expression gives us the quadratic equation:
\[
x^2 + 4x - 3x - 12 = 0
\]
Combining like terms, we get:
\[
x^2 + x - 12 = 0
\]
So, the quadratic equation in reduced factored form is \( x^2 + x - 12 = 0 \).
(x - 3)(x + 4) = 0
=================
To write a quadratic equation with two given solutions, such as 3 and -4, we use the fact that if 'r' is a root of a quadratic equation, then (x - r) is a factor of the equation.
Therefore, for the solutions 3 and -4, the factors are (x - 3) and (x + 4). The polynomial in reduced factored form is obtained by multiplying these factors:
- (x - 3)(x + 4)
The quadratic equation is therefore:
- (x - 3)(x + 4) = 0